Information Network Villages: A community-focused digital divide reduction policy in rural Korea - Jung, Man Chul; Park, Sora; Lee, Jee Young (Journal of Telecommunications and the Digital Economy, 2014)
This study examines South Korea’s Information Network Village (INVIL) project as an exemplary policy of building sustainable communities through a digital divide policy implemented in small rural areas. INVIL project has three objectives: to close the digital gap between urban and rural areas, to create new sources of revenues from existing industries, and to build sustainable local communities. The conception was that rural digital divide can only be resolved by addressing deep rooted rural issues that influence the provision and adoption of ICT. While the INVIL programs may not remedy the gap in the short term, it provides a future vision to the communities. Due to this multi-layered and long term approach, the villages have been successful in narrowing the digital divide, not only in terms of access but also in effectively utilising broadband to enhance the local economy and building sustainable communities. This paper introduces the INVIL project, the plans and outcomes, as well as a qualitative evaluation of the process across a decade. Following a general description of the project, an in-depth case study of three successful INVILs is provided. The uniqueness of the program is that it emphasises investment in human capital rather than on infrastructure and includes a tailored vision of each local community. This motivates local residents to be active participants, which is the key to the success of the policy.